The Effect of the Otof (One Team Student One Family) Model on Knowledge of Mothers and Toddlers to Prevent Stunting - Desi Yanuar Trianita; Atik Pramesti Wilujeng; Akhmad Yanuar Fahmi Pamungkas (Global Health Science Group, 2022)
The incidence of stunting is caused by several factors, one of which is the family factor. Mothers as the main caregivers for toddlers have a very important role in preventing stunting in children. Efforts to improve mothers' knowledge and skills in preventing stunting in toddlers continue to be carried out, but innovation is needed to increase mothers' understanding of the growth and development of toddlers so that stunting in toddlers can be prevented. One of the educational method innovations that can be carried out effectively is based on empowerment, namely 1 student 1 family, but there has been no research on a student team 1 family. The purpose of this study was to determine the effect of the OTOF (One Team Student One Family) model on the level of knowledge among mothers of toddlers. This research was conducted in the working area of ​​the Kertosari Public Health Center, Banyuwangi Regency from the beginning of June to the end of October using a pre and post test Quasy Experiment with group control and using an independent t test. The population is all mothers who have toddlers. Sampling with stratified random sampling technique 61 respondents consisting of 31 interventions and 30 controls. The data collection instrument in the form of a questionnaire that has been declared valid and reliable the intervention used is to empower Health students (Nursing, Analyst, Midwifery, Pharmacy and Nutrition) according to their ability to carry out Health Education to 1 family. The instruments used in this study were Questionnaires and SOPs . The results showed that after giving the OTOF Model treatment the knowledge of the mother of toddlers increased and after being tested with the Paired T Test, the result was p = 0.00 which means that there is an effect. The conclusion is the results of the study show that there is an effect of the OTOF Model on the knowledge of mothers of children under five.